2021
DOI: 10.17509/jaset.v13i2.37212
|View full text |Cite
|
Sign up to set email alerts
|

Fintech Payment Adoption Among Micro-Enterprises: The Role of Perceived Risk and Trust

Abstract: The current adoption of fintech payment technology by MSMEs is motivated by the trend of using digital money. This study presents an investigation the factors that influence the intention to use fintech payments (e-money, e-wallet and Electronic Data Capture) in micro-enterprises. Furthermore, this study will explore more specifically the role and perceived trust and risk in fintech payment adoption. This study uses a quantitative method by distributing surveys to 136 Micro, Small and Medium Enterprises using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…They found that education about technology, access to credit, and provision of government incentives are critical for enhancing the adoption rates of technology. Other factors identified in a study on fintech adoption in the SMME sector include perceived usefulness of applications, concerns of risk, and that of trust (Purwantini & Anisa 2021).…”
Section: Information and Communication Technology Adoption Among Micr...mentioning
confidence: 99%
“…They found that education about technology, access to credit, and provision of government incentives are critical for enhancing the adoption rates of technology. Other factors identified in a study on fintech adoption in the SMME sector include perceived usefulness of applications, concerns of risk, and that of trust (Purwantini & Anisa 2021).…”
Section: Information and Communication Technology Adoption Among Micr...mentioning
confidence: 99%
“…Perceived usefulness refers to the extent to which entrepreneurs perceive fintech as beneficial for improving business processes, increasing operational efficiency, and achieving business objectives. For SMEs in Surabaya, understanding the perceived usefulness of fintech solutions may shed light on the extent to which these technologies align with their specific business needs and goals (Ryu,2018;Purwantini et al, 2021).…”
Section: Table 1 Number Of Msmes In Surabaya City (2020-2022)mentioning
confidence: 99%
“…In Surabaya's business landscape, SMEs' trust in fintech platforms plays a pivotal role in shaping their willingness to adopt these technologies. Factors such as data security measures, transactional transparency, and the reputation of fintech providers contribute to building trust among SME entrepreneurs, thereby influencing their adoption decisions (Purwantini et al, 2021;Zhong et al, 2019;Chan et al, 2022) Financial risk represents a critical consideration for SMEs contemplating fintech adoption. Financial risk entails the potential monetary losses or costs associated with utilizing fintech solutions, including transaction fees, operational expenses, and cybersecurity threats.…”
Section: Table 1 Number Of Msmes In Surabaya City (2020-2022)mentioning
confidence: 99%